2015
DOI: 10.1371/journal.pone.0121334
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Click-Compatible Monolignol Probe to Study Lignin Deposition in Plant Cell Walls

Abstract: Lignin plays important structural and functional roles in plants by forming a hydrophobic matrix in secondary cell walls that enhances mechanical strength and resists microbial decay. While the importance of the lignin matrix is well documented and the biosynthetic pathways for monolignols are known, the process by which lignin precursors or monolignols are transported and polymerized to form this matrix remains a subject of considerable debate. In this study, we have synthesized and tested an analog of conife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…In principle, dual labeling studies with our approach can also be extended to other biomolecules by using two distinct modified precursors of plant cell wall polymers - including all three main monolignols or their metabolic precursors as well as various monosaccharides that constitute the polysaccharide matrix. Since its inception, bioorthogonal chemistry has indeed been mainly developed to investigate glycans/polysaccharides through metabolic oligosaccharide engineering (MOE) 4 5 17 28 , but surprisingly there have been only very few applications to plant biology so far 7 8 9 10 11 12 . In terms of compatibility of the reactions, the study of lignin was indeed a complex case to solve as both chemical reporters are incorporated into the same reticulated polymer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, dual labeling studies with our approach can also be extended to other biomolecules by using two distinct modified precursors of plant cell wall polymers - including all three main monolignols or their metabolic precursors as well as various monosaccharides that constitute the polysaccharide matrix. Since its inception, bioorthogonal chemistry has indeed been mainly developed to investigate glycans/polysaccharides through metabolic oligosaccharide engineering (MOE) 4 5 17 28 , but surprisingly there have been only very few applications to plant biology so far 7 8 9 10 11 12 . In terms of compatibility of the reactions, the study of lignin was indeed a complex case to solve as both chemical reporters are incorporated into the same reticulated polymer.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fast-growing popularity of this powerful method in bacterial and animal cells, reports describing its use in plant biology are surprisingly few and far between 7 8 9 10 11 12 . We were particularly interested in applying this strategy in plants to study the formation of lignin, one of the most prevalent biopolymers on the planet and a major component of lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Primary cell walls are composed of cellulose microfibrils and structural proteins [ 69 ]. Secondary cell walls are less flexible than primary cell walls and contain lignin [ 70 ]. In this experiment, VA and VC exhibited limited DE of genes involved in primary cell wall deposition when grown at higher pH.…”
Section: Discussionmentioning
confidence: 99%
“…Click chemistry was recently used to label cells undergoing DNA synthesis while following a Golgi protein marker fused to a fluorescent protein (Bourge et al ., ). Several recent studies have reported the imaging of plant cell wall components using a click chemistry approach and two groups have recently reported the imaging of plant cell wall lignification using different azido‐ and alkynyl‐tagged monolignol analogues (Bukowski et al ., ; Tobimatsu et al ., ; Pandey et al ., ). In addition, an alkyne derivative of L‐fucose (Fuc‐Al) has been used for cell wall labelling in Arabidopsis thaliana (Anderson et al ., ).…”
Section: Introductionmentioning
confidence: 97%